2003
DOI: 10.1093/bjc/43.2.269
|View full text |Cite
|
Sign up to set email alerts
|

Racism, Ethnicity and Criminology. Developing Minority Perspectives

Abstract: In empirical and theoretical criminology references to racism and ethnicity are commonplace, although much discussion has centred on the narrowly defined 'race and crime' debate. In an attempt to move beyond this debate, which is focused on whether certain ethnic minorities are over-represented in the prison population because of elevated rates of offending or because of discriminatory treatment in the criminal justice system, this paper proposes the formulation of minority perspectives in criminology.These wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 47 publications
(41 reference statements)
0
78
0
1
Order By: Relevance
“…Among any deprived categories, researchers on youth and juvenile delinquencies tend to either focus on why certain youths commit crimes (Owumi, 1994;Omitoogun, 1996) -or alternatively on young males' continued oppression and criminalization by the society, police and criminal justice system (Phillips and Bowling, 2003). Within this paper I have, following Gunter's study (2008) among black deprived youths in East London focused on exploring the notion of deviance through detailing its impact and influence on the everyday lived experiences of those young street children, with difficult childhood which I termed 'growing up poor' residing in Lagos central neighbourhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among any deprived categories, researchers on youth and juvenile delinquencies tend to either focus on why certain youths commit crimes (Owumi, 1994;Omitoogun, 1996) -or alternatively on young males' continued oppression and criminalization by the society, police and criminal justice system (Phillips and Bowling, 2003). Within this paper I have, following Gunter's study (2008) among black deprived youths in East London focused on exploring the notion of deviance through detailing its impact and influence on the everyday lived experiences of those young street children, with difficult childhood which I termed 'growing up poor' residing in Lagos central neighbourhood.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed when looking specifically at research exploring poverty, deviance, offending and victimization within neighbourhoods, Garland et al (2006: 423) similarly note that 'there has been a tendency within this work to make sweeping assumptions' about those groups that fall under the broad 'catch-all' 'poor' and 'deviance' categories often referred to in academic and official government agency reports. Phillips and Bowling (2003) also point out that criminologists interested in street youths have tended to view the disproportionate numbers of the poor individuals caught up within the criminal justice system as being either symptomatic of their higher rates of offending or because of institutionalized neglect. The suggested alternative to the above 'either/or' youth deviance conundrum is the development of 'minority perspectives' within the field of criminology that might contribute to a more multidimen-sional approach to understanding touts' experience of victimisation, offending, [and] criminal justice processing.…”
Section: Introductionmentioning
confidence: 99%
“…This study used a minority perspective approach (see Phillips and Bowling 2003); it did not seek to reinforce Pakistani Kashmiri British Muslims' 'otherness' through highlighting the 'Muslim' in Pakistani Kashmiri British Muslims but rather through emphasising no identity in the questions participants were asked, provided a platform where the 'British' and the 'us' could also be articulated.…”
Section: Research and Methodsmentioning
confidence: 99%
“…Minorities' and migrants' experiences and perceptions are vastly underexplored in contemporary quantitative criminological research due, in the most part, to the immense challenge and expense of doing so (see Phillips and Bowling, 2003). The present research therefore attempted to fill this void by capturing the perspectives and experiences of both the local established residents (subsequently termed the 'local' group) and the new Polish migrants (subsequently termed the 'migrant' group).…”
Section: The Methodological Approachmentioning
confidence: 99%
“…While some have suggested that this 'new' migration has "gone some way to decoupling the issue of immigration from that of race" (The Economist, 2008: 33), the perceived association of 'immigrants', 'strangers' or 'outsiders' with a disruption to social order remains a prevalent research issue (Elias and Scotson, 1965). There is a plethora of research on the negative attitudes of majority or 'established' populations towards the 'immigrant' or the 'stranger' (Hughes, 2007); yet there remains little criminological research on the lived experiences and subjectivities of new migrant communities themselves (Phillips and Bowling, 2003). The contribution of this paper therefore is to provide one of the few empirical and in-depth case studies that explores how both 'established' residents and new migrants perceive, adapt and negotiate their social relationships with each other in their day to day lives.…”
mentioning
confidence: 99%